Pendekatan Participatory Action Research (PAR) dalam Pemberdayaan Masyarakat Desa Pusakasari Kabupaten Ciamis - Chandra, Deni; Rifai, Ahmad; Rizkiyatusholihah, Rizkiyatusholihah; Kania Dewi, Eva (Journal of Empowerment Community, 2026)
The community service activity through the Student Community Service Program in Pusakasari Village, Cipaku District, Ciamis Regency, was initiated in response to several local issues such as low educational literacy, limited waste management, underutilized local potential, and lack of innovation in economic and tourism development. This program aimed to improve the community’s quality of life through empowerment based on local potential and active community participation. The method applied was a participatory approach using the Participatory Action Research model involving observation, community discussions, potential mapping, and the implementation of multidisciplinary programs. The results showed increased community awareness of environmental management, enhanced skills of small business owners in product packaging and digital marketing, and improved student motivation through creative educational activities. In addition, the community began to take part in developing Cibayawak Natural Tourism and preserving the SILARIA cultural tradition as a local cultural asset. In conclusion, this program successfully fostered collaboration between the university and the local community in building an independent, healthy, and sustainable village.